New insights into molecular mechanisms of epigenetic regulation in kidney disease. (December 2016) - Mimura, Imari; Tanaka, Tetsuhiro; Nangaku, Masaomi
Summary: The number of patients with kidney failure has increased in recent years. Different factors contribute to the progression of chronic kidney disease, including glomerular sclerosis, atherosclerosis of the renal arteries and tubulointerstitial fibrosis. Tubulointerstitial injury is induced by hypoxia and other inflammatory signals, leading to fibroblast activation. Technological advances using high‐throughput sequencing has enabled the determination of the expression profile of almost all genes, revealing that gene expression is intricately regulated by DNA methylation, histone modification, changes in chromosome conformation, long non‐coding RNAs and microRNAs. These epigenetic modifications are stored as cellular epigenetic memory. Epigenetic memory leads to adult‐onset disease or ageing in the long term and may possibly play an important role in the kidney disease process. Herein we emphasize the importance of clarifying the molecular mechanisms underlying epigenetic modifications because this may lead to the development of new therapeutic targets in kidney disease.